A CROSS SECTIONAL STUDY ABOUT FACTORS ASSOCIATED WITH HEALTH FACILITY DELIVERIES AMONG WOMEN OF REPRODUCTIVE AGE IN THE CATCHMENT AREAS OF KALISIZO HOSPITAL, KYOTERA DISTRICT. - Jackline Nyangoma (Student's Journal of Health Research, 2023)
Background This study aims to determine the factors associated with health facility deliveries among women of reproductive age in the catchment areas of Kalisizo Hospital, kyotera Methodology This study was conducted in Kyotera, southwest of Masaka, around Kalisizo Hospital. The study population included all mothers (15-49 years) who had attended antenatal care. This study used cross-sectional, mixed methods. Results Women in older age groups 25-29years (APR = 2.339 95% CI:0.120 - 8.56) and 30-34years (APR = 2.676 95% CI:0.600 - 12.38) had a higher likelihood of health facility deliveries compared to adolescents aged 15-19years (APR = 0.499 95% CI:0.050 - .999). Mothers who delayed setting off for delivery after experiencing increased labor pains were likelier to have health facility deliveries (APR = 8.455 95% CI:3.024 - 23.636) than those who immediately set off when they felt labor pains. Most of the participants who had no MCH visits by community health workers in their households were less likely to have health facility deliveries compared to those with such visits (APR= 48.462 95% CI:6.511 - 360.714). Factors include delays in mothers deciding to have a health facility delivery or reaching the health facility in time, skills gaps among birth attendants in the provision of emergency obstetric and newborn care services (EMONC), and more community behavioral practices related to decisions on health facility deliveries. Conclusion Mother's attendance of ANC during pregnancy, marital status, and mother's gravidity/parity, availability of skilled birth attendants, MCH visits by community health workers, the experience of complications during and after labor, and set off time during labor to the delivery place were significant determinants of health facility deliveries. Recommendation Programs promoting health facility births in similar settings should prioritize boosting ANC attendance, MCH visits by community health workers, and improving the experiences of mothers at maternal and antenatal wards.